Eliciting individual preferences for pension reform - Yosr Abid Fourati; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2009)
Pension systems have recently been under scrutiny because of the expected population ageing threatening its sustainability. This paper's contribution to the debate is from a political economic perspective as it uses data from a choice experiment to investigate individual preferences for an alternative state pension scheme based around preferences for cost, poverty, retirement age and pension parameters. Answers are used to estimate a lifecycle utility model of preferences towards pensions' parameters. Results suggest that individuals' value orientation is an important determinant of their preferences. Respondents' income determines which degree of redistribution is preferred. However, preferences according to age are in contradiction with what is suggested in theory.
urn:nbn:de:101:1-20091019286
Keywords: H0; I3; 330; Population ageing; pension system reform; redistribution; stated preferences; Gesetzliche Rentenversicherung; Rentenreform; Einkommensumverteilung; Offenbarte Präferenzen; Alternde Bevölkerung; Lebenszyklus; Irland